A literature review on the detection and tracking of obstacles applied for Advanced Driver Assistance Systems (ADAS) in Robotic Vehicle - Bruno, Diego Renan; Osório, Fernando Santos (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
The potential of an intelligent computer vision system to detect and predict the actions of dynamic agents on the streets is applied to increase traffic safety with intelligent robotic vehicles. In this paper we present a systematic review involving computer vision models with 2D and 3D data fusion for the detection and tracking of obstacles in traffic environments.The studies highlighted by this review, present the main positive and negative points of the state-of-the-art for detecting and tracking obstacles in works of Visual Robotic Attention. The results presented should enable an advance for research in the area of Advanced Driver Assistance Systems (ADAS) and Autonomous Vehicles.